2015
DOI: 10.1074/jbc.m115.636506
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-T Cell Interactions Mediate Neuropathic Pain through the Glucocorticoid-induced Tumor Necrosis Factor Ligand System

Abstract: Peripheral neuroinflammation caused by activated immune cells can provoke neuropathic pain. Herein, we investigate the actions of macrophages and T cells through glucocorticoid-induced tumor neurosis factor receptor ligand (GITRL) and its receptor (GITR) in neuropathic pain. After partial sciatic nerve ligation (PSL) in enhanced green fluorescent protein (eGFP) chimeric mice generated by the transplantation of eGFP(+) bone marrow cells, eGFP(+) macrophages, and T cells markedly migrated to the injured site aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 33 publications
2
89
0
Order By: Relevance
“…This suggests that macrophages may play a pivotal role in the regulation of neuroinflammation and pathologic pain. Notably, the ablation or inhibition of macrophages results in the prevention of experimental neuropathic pain in rodents (Liu et al, 2010;Echeverry et al, 2013;Kiguchi et al, 2014;Kobayashi et al, 2015). Macrophages are often polarized toward functionally distinct phenotypes to regulate complicated inflammatory processes (Ricardo et al, 2008;Murray and Wynn, 2011;Wynn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that macrophages may play a pivotal role in the regulation of neuroinflammation and pathologic pain. Notably, the ablation or inhibition of macrophages results in the prevention of experimental neuropathic pain in rodents (Liu et al, 2010;Echeverry et al, 2013;Kiguchi et al, 2014;Kobayashi et al, 2015). Macrophages are often polarized toward functionally distinct phenotypes to regulate complicated inflammatory processes (Ricardo et al, 2008;Murray and Wynn, 2011;Wynn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous reports have demonstrated that the infiltration of circulating leukocytes (i.e., monocytes/macrophages and neutrophils) to the damaged nervous system contributes significantly to chronic neuroinflammation (Liu et al, 2000;Hu and McLachlan, 2002;Thacker et al, 2007; Austin and Moalem-Taylor, 2010;Calvo et al, 2012). Particularly, macrophages account for the largest population among infiltrating leukocytes in injured peripheral nerves, and the depletion of macrophages clearly prevents experimental neuropathic pain in rodents (Liu et al, 2000;Mert et al, 2009;Kobayashi et al, 2015). Moreover, it has been reported that several inflammatory cytokines [e.g., interleukin (IL)-1b and tumor necrosis factor a (TNFa)] and chemokines [e.g., CC-chemokine ligand (CCL) 3 and CCL4], derived from inflammatory macrophages, exert functions as key neuroinflammatory regulators that directly enhance the excitability of primary sensory neurons and prolong neuroinflammation, facilitating neuropathic pain (Sommer and Kress, 2004;Scholz and Woolf, 2007;Lee and Zhang, 2012;Saika et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are sentinel myeloid cells present throughout the body, and monocytes are blood-borne myeloid cells prominently recruited to inflammatory sites during tissue injury. A role for macrophages and monocytes in chronic painful disease conditions has been extensively demonstrated [1014]. These cells produce many inflammatory cytokines, growth factors, and lipids that can act directly on nociceptor neurons to increase pain (Figure 1).…”
Section: Modulation Of Pain Sensitivity By Immune Cellsmentioning
confidence: 99%
“…Animal studies have enlightened the role of T cells in pain development. In particular, the depletion of CD4 + T cells in a mouse model was able to inhibit thermal hyperalgesia and tactile central sensitization following partial sciatic nerve ligation [57,58].…”
Section: Role Of T Cells In Fibromyalgia: Literature Datamentioning
confidence: 99%